2019
DOI: 10.2478/otmcj-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Overview of construction simulation approaches to model construction processes

Abstract: Abstract Construction simulation is a versatile tech­nique with numerous applications. The basic simulation methods are discrete-event simulation (DES), agent-based modeling (ABM), and system dynamics (SD). Depending on the complexity of the problem, using a basic simulation method might not be enough to model construction works appropriately; hybrid approaches are needed. These are combinations of basic methods, or pairings with other techniques, such as fuzzy logic (FL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(76 reference statements)
0
16
0
Order By: Relevance
“…Hybrid simulation approaches can be used for obtaining these. After selecting the most appropriate approach and determining the structure of the model, the input data need to be collected [42]. This is a crucial step as the output will only be as good as the input.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid simulation approaches can be used for obtaining these. After selecting the most appropriate approach and determining the structure of the model, the input data need to be collected [42]. This is a crucial step as the output will only be as good as the input.…”
Section: Resultsmentioning
confidence: 99%
“…After the input data are available, the next step is to create the model and run the simulation [42]. Based on initial results, it needs to be refined, then verified and validated with data from real-life projects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Kaissy et al (2019) reviewed CSM methods used in construction research and found that three simulation paradigms have been used: Discrete Event Simulation (DES), Agent-Based Modeling (ABM) and System Dynamics (SD). The use of hybrid simulation paradigms has also been discussed in construction literature (Naraghi et al 2017;Bokor et al 2019). Moreover, simulation-based optimization is becoming a popular topic among construction researchers nowadays (González et al 2009;Zaki et al 2019).…”
Section: Csmmentioning
confidence: 99%
“…The accurate prediction of the compaction duration can contribute to effective construction organization management and resource planning. The discrete event simulation (DES) method, as a popular tool in the civil engineering construction field [ 3 , 4 , 5 , 6 , 7 ], can achieve operation duration prediction by simulating the detailed resource flow based on the concept of entity and event. When building a construction simulation model, both the input parameter model and state transition conditions of resources are essential prerequisites and have a significant impact on the reliability of the model [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%